The site of Saar : Dilmun reconsidered - Crawford, Harriet
Recent excavations at the site of Saar, Bahrain, further advance our knowledge of Dilmun, that magical place on the Gulf which was a cross-roads of southwest Asian land and northwest Indian Ocean. Saar is a proto-urban agglomeration with the characteristics of a planned settlement Ñ planned it appears from some other and controlling place